Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.33005/ebgc.v3i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Shopping Orientation and Online Trust to Enhance Online Purchase Intentions With Gender Differences as Moderator

Abstract: The use of the internet now seems to have become a primary need. The growth of e-commerce in Indonesia is driving the popularity of non-cash transactions. The purpose of this study, first to give an overview and the implications of the influence of shopping orientation and trust in online consumer purchase intentions. Second, see gender differences as moderating variables because in the virtual group by gender plays a role in communication and e-commerce transactions. Purposive random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Moreover, empirical evidence suggests that individuals of the male gender have a higher propensity for risky decision-making and display a lower inclination toward brand trust than their female counterparts (Lu et al, 2021). Gender differences influence e-commerce transactions to particular businesses and consumers' trust in their brand (Murphy and Tocher, 2011;Effendi et al, 2020). Earlier studies found that female consumers were more influential on brand trust than male consumers (Ratnasari et al, 2020;Xue et al, 2020).…”
Section: Moderating Effect Of Demographic Characteristicsmentioning
confidence: 99%
“…Moreover, empirical evidence suggests that individuals of the male gender have a higher propensity for risky decision-making and display a lower inclination toward brand trust than their female counterparts (Lu et al, 2021). Gender differences influence e-commerce transactions to particular businesses and consumers' trust in their brand (Murphy and Tocher, 2011;Effendi et al, 2020). Earlier studies found that female consumers were more influential on brand trust than male consumers (Ratnasari et al, 2020;Xue et al, 2020).…”
Section: Moderating Effect Of Demographic Characteristicsmentioning
confidence: 99%
“…Dampak e-commerce terhadap perekonomian Indonesia sangat signifikan, dengan negara ini mengalami pertumbuhan yang belum pernah terjadi sebelumnya di sektor ini. Pertumbuhan ecommerce di Indonesia didorong oleh meningkatnya popularitas transaksi non-tunai, pertumbuhan kelas menengah di negara ini, dan populasi muda yang melek teknologi yang telah merangkul belanja online (Azzery, 2022;Effendi et al, 2020). Ekonomi digital, khususnya e-commerce, telah memberikan kontribusi yang signifikan terhadap Produk Domestik Bruto (PDB) Indonesia (Pratiwi, n.d.).…”
Section: Pendahuluanunclassified